Job stress and burnout among ideological and political education teachers during the COVID-19 pandemic: A moderated mediation model - Shang, Weiwei (Frontiers in Psychology, 2022)
Job burnout among ideological and political education (IPE) teachers in China is a complex problem and rewarding area of research. This study explored the relationship between job stress and burnout among ideological and political education (IPE) teachers in the context of the COVID-19 pandemic. The cross-sectional design included a sample of self-report measures sampled from 362 university IPE teachers. Using multiple line regression analysis, our main findings were as follows: first, job stress had a significant predictive effect on work–family conflict and job burnout; second, work–family conflict mediated the relationship between job stress and job burnout; and finally, resilience productively moderated the relationships between job stress and both work–family conflict and burnout. These results suggest that resilient IPE teachers are less likely to suffer from burnout. They indicate the need to systematically foster resilience in trainees and experienced instructors as a means of coping with adverse work conditions.